Antibacterial and Bioactive 3D-Printed Hexagonal Boron Nitride Incorporated Gelatin/Methyl Cellulose Scaffolds for Bone Tissue Engineering Applications - Karaca, Mehmet Ali; Yilmaz, Ilknur; Ozbek, Tulin; Guven, Alper; Kafes, Gokhan; Gok, Ozgul; Ege, Duygu (WILEY-V C H VERLAG GMBH, 2026)
In this study, we fabricated 3D-printed scaffolds based on gelatin (GEL), methylcellulose (MC), and varying concentrations of hexagonal boron nitride h-BN nanoplatelets. The GEL/MC/BN hydrogel inks were prepared with optimized rheological properties for extrusion-based 3D printing and chemically crosslinked using EDC/NHS. The printability, pore fidelity, and strut geometry of the scaffolds were characterized, revealing consistent architectures with adequate mechanical robustness. FTIR, swelling behavior, degradation, and contact angle measurements demonstrated successful h-BN nanoplatelet incorporation and favorable hydrogel network stability. Mechanical tests indicated that h-BN nanoplatelet addition preserved the compressive modulus and flexibility. In vitro assays using MC3T3-E1 pre-osteoblasts demonstrated that the scaffolds supported % cell viability and proliferation. Remarkably, h-BN nanoplatelet incorporation triggered calcium phosphate formation both in SBF and Alizarin Red staining studies. FTIR and SEM-EDS analysis demonstrated that apatite formation was triggered with h-BN. Apatite formation is possibly due to the negative charge of h-BN nanoplatelets in the medium which triggered calcium phosphate deposition. Antibacterial testing against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus revealed a significant, species-specific bactericidal effect at >= 5% BN content, especially against Gram-negative strains. Overall, these findings indicate the potential of h-BN-incorporated GEL/MC scaffolds as a promising platform for infection-resistant, cytocompatible, and structurally stable bone grafts.
Keywords: 3D printing; antibacterial properties; biomineralization; hexagonal boron nitride; methyl cellulose; Materials Science; Polymer Science